Hypoventilation Training at Supramaximal Intensity Improves Swimming Performance. Issue 6 (June 2016) - WOORONS, XAVIER; MUCCI, PATRICK; RICHALET, JEAN PAUL; PICHON, AURÉLIEN
ABSTRACT: Purpose: This study aimed to determine whether hypoventilation training at supramaximal intensity could improve swimming performance more than the same training conducted under normal breathing conditions. Methods: For a 5-wk period, 16 triathletes (12 men and 4 women) were asked to include one supramaximal set of 12 to 20 × 25-m front crawl swimming twice a week into their usual swimming session, performed either with hypoventilation at low lung volume (VHL group) or with normal breathing (CONT group). Before (Pre) and after (Post) training, all triathletes performed all-out front crawl trials for 100, 200, and 400 m. Results: Time performance was significantly improved in VHL in all trials (100 m: −3.7 ± 3.7 s [−4.4% ± 4.0%]; 200 m: −6.9 ± 5.0 s [−3.6% ± 2.3%]; 400 m: −13.6 ± 6.1 s [−3.5% ± 1.5%]) but did not change in CONT. In VHL, the maximal lactate concentration (+2.35 ± 1.3 mmol·L −1 on average) and the rate of lactate accumulation in blood (+41.7% ± 39.4%) were higher at Post than at Pre in the three trials, whereas they remained unchanged in CONT. Arterial oxygen saturation, heart rate, breathing frequency, and stroke length were not altered in both groups at the end of the training period. On the other hand, stroke rate was higher at Post compared with Pre in VHL but not different in CONT. The measurements of gas exchange for the 400-m trial revealed no change in peak oxygen consumption as well as in any pulmonary variable in both groups. Conclusion: This study demonstrated that VHL training, when performed at supramaximal intensity, represents an effective method for improving swimming performance, partly through an increase in the anaerobic glycolysis activity.